Deriving ICD‐11 personality disorder domains from dsm‐5 traits: initial attempt to harmonize two diagnostic systems. (15th May 2017) - Bach, B.; Sellbom, M.; Kongerslev, M.; Simonsen, E.; Krueger, R. F.; Mulder, R.
Abstract : Objective: The personality disorder domains proposed for the ICD‐11 comprise Negative Affectivity, Detachment, Dissociality, Disinhibition, and Anankastia, which are reasonably concordant with the higher‐order trait domains in the Alternative DSM‐5 Model for Personality Disorders. Method: We examined (i) whether designated DSM‐5 trait facets can be used to describe the proposed ICD‐11 trait domains, and (ii) how these ICD‐11 trait features are hierarchically organized. A mixed Danish derivation sample ( N = 1541) of 615 psychiatric out‐patients and 925 community participants along with a US replication sample ( N = 637) completed the Personality Inventory for DSM‐5 (PID‐5). Sixteen PID‐5 traits were designated to cover features of the ICD‐11 trait domains. Results: Exploratory structural equation modeling (ESEM) analyzes showed that the designated traits were meaningfully organized in the proposed ICD‐11 five‐domain structure as well as other recognizable higher‐order models of personality and psychopathology. Model fits revealed that the five proposed ICD‐11 personality disorder domains were satisfactorily resembled, and replicated in the independent US sample. Conclusion: The proposed ICD‐11 personality disorder domains can be accurately described using designated traits from the DSM‐5 personality trait system. A scoring algorithm for the ICD‐11 personality disorder domains is provided inappendix .